THE ROLE OF USER-GENERATED IMAGES AND SELLER TRUST IN SHAPING GENERATION Z PURCHASE INTENTION - Dwi Anugrah Setiawati; Astri Wulandari; Alma Syifa Maulidina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of user-generated images and seller trust on purchase intention among Generation Z Shopee users in Indonesia. The rapid growth of e-commerce has increased consumers’ reliance on visual information and online seller credibility when making purchase decisions. This research applies a quantitative explanatory approach using an online survey of 101 respondents aged 18–27 who actively shop on Shopee. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships between variables. The results show that user-generated images significantly enhance purchase intention by improving perceptions of product authenticity and reliability. In addition, seller trust positively influences purchase intention by reducing perceived risk and increasing confidence in online transactions. Both variables jointly contribute to shaping Generation Z’s purchasing behavior in digital marketplaces. This study provides empirical evidence on the role of visual content and trust in e-commerce decision-making, offering practical insights for online sellers to optimize review management and trust-building strategies.